Chemoembolization of hepatocellular carcinoma with HepaSphere™. (April 2015) - Malagari, Katerina; Pomoni, Anastasia; Filippiadis, Dimitrios; Kelekis, Dimitrios
SUMMARY : This review discusses the current data on Hepasphere™ in the treatment of hepatocellular carcinoma. HepaSphere is a drug-loadable microsphere that can be bound with doxorubicin, epirubicin, cisplatin or oxaliplatin. In vitro and in vivo studies confirm lower systemic exposure to the drug and fewer systemic doxorubicin-related side effects. Studies suggest that this technique is better tolerated than conventional lipiodol-based chemoembolization (c-TACE). In intermediate and early stage hepatocellular carcinoma – nonresponsive to curative treatments – complete response and partial response rates range from 22.2 to 48% and 43.7 to 51%, respectively. Studies with survival as an end-point are needed and head-to-head comparisons with other drug-eluting beads are necessary.